Krzysztof Beck Model of Two Economies and Results of the Research into Economic Cycles Synchronisation – Theoretical and Empirical Verification (Economic and Political Thought, 2014)
The main aim of this paper is to engage in a problem of unclear outcomesof empirical research on business cycle synchronization. In order to achievethat, the author presents a model of two economies, which provides veryclear tips on shock transmission mechanisms and necessary control variablesfor the need of econometric evaluation. The presented model shows thatthe impact of international trade transmission channel, approximated bymarginal propensity to consumption, is positive, but exhibits diminishinginfluence of business cycle synchronization. This conclusion was reachedearlier by Silvestre, Mendonça and Passos (2007), and confirmed by theauthor with the use of nonparametric methods. The model of two countrieshas also proved that while analysing business cycle synchronization, controlis necessary because of the symmetry of shocks distribution, fiscal policycorrelation and exchange rate regime. Empirical verification with the use ofparametrical methods revealed correctness of the statements, as well as thenecessity of control due to monetary policy correlation. On this basis, theauthor was able to explain the results reached by Baxter and Kouparitsas(2004), as well as Böwer i Guillemineau (2006).